Differential susceptibility of cortical and subcortical inhibitory neurons and astrocytes in the long term following diffuse traumatic brain injury. Issue 17 (26th April 2016) - Carron, Simone F.; Yan, Edwin B.; Alwis, Dasuni S.; Rajan, Ramesh
Abstract : Long‐term diffuse traumatic brain injury (dTBI) causes neuronal hyperexcitation in supragranular layers in sensory cortex, likely through reduced inhibition. Other forms of TBI affect inhibitory interneurons in subcortical areas but it is unknown if this occurs in cortex, or in any brain area in dTBI. We investigated dTBI effects on inhibitory neurons and astrocytes in somatosensory and motor cortex, and hippocampus, 8 weeks post‐TBI. Brains were labeled with antibodies against calbindin (CB), parvalbumin (PV), calretinin (CR) and neuropeptide Y (NPY), and somatostatin (SOM) and glial fibrillary acidic protein (GFAP), a marker for astrogliosis during neurodegeneration. Despite persistent behavioral deficits in rotarod performance up to the time of brain extraction (TBI = 73.13 ± 5.23% mean ± SEM, Sham = 92.29 ± 5.56%, P < 0.01), motor cortex showed only a significant increase, in NPY neurons in supragranular layers (mean cells/mm 2 ± SEM, Sham = 16 ± 0.971, TBI = 25 ± 1.51, P = 0.001). In somatosensory cortex, only CR + neurons showed changes, being decreased in supragranular (TBI = 19 ± 1.18, Sham = 25 ± 1.10, P < 0.01) and increased in infragranular (TBI = 28 ± 1.35, Sham = 24 ± 1.07, P < 0.05) layers. Heterogeneous changes were seen in hippocampal staining: CB + decreased in dentate gyrus (TBI = 2 ± 0.382, Sham = 4 ± 0.383, P < 0.01), PV + increased in CA1 (TBI = 39 ± 1.26, Sham = 33 ± 1.69, P < 0.05) and CA2/3 (TBI = 26 ± 2.10, Sham = 20 ± 1.49, P < 0.05), and CR + decreased in CA1 (TBI = 10 ± 1.02, Sham = 14 ± 1.14, P < 0.05). Astrogliosis significantly increased in corpus callosum (TBI = 6.7 ± 0.69, Sham = 2.5 ± 0.38; P = 0.007). While dTBI effects on inhibitory neurons appear region‐ and type‐specific, a common feature in all cases of decrease was that changes occurred in dendrite targeting interneurons involved in neuronal integration. J. Comp. Neurol. 524:3530–3560, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using immunohistochemistry the authors demonstrate a selective loss of subsets of interneurons in cortex and hippocampus suggesting the differential susceptibility of inhibitory neurons to trauma and reflective of the consequences of trauma induced network excitation/inhibition imbalance.